OPTIMIZATION OF GRAFTING TECHNIQUES USING TRICHODERMA ON LIBERICA COFFEE IN SAMBAS - Wilis Widi Wilujeng (Adisam Publisher, 2026)
Sambas Liberica coffee holds significant strategic value as a leading local commodity. The main challenge on the ground is low productivity due to suboptimal propagation techniques. Many farmers still rely on generative propagation (from seeds), which results in plants with inconsistent traits and suboptimal growth. Vegetative propagation has the potential to accelerate the regeneration of high-quality, uniform plants. High-quality coffee seedlings can be obtained through vegetative propagation using the shoot-grafting method. There is a need to identify the most effective vegetative propagation technique for Sambas Liberica coffee. This study aims to determine the optimal propagation technique based on germination and growth success rates. In this study, vegetative propagation techniques will be tested, specifically top-grafting, as well as the use of Trichoderma-treated growing media. The research was conducted in the greenhouse of the Agribusiness Department at the Sambas State Polytechnic. The study subjects were Liberica coffee seedlings; the rootstocks were 7-month-old seedlings, and the scions were obtained from Liberica coffee parent trees in Kartiasa Village. The experimental design used in this study was a two-factor completely randomized design (CRD) with three replicates. The results showed that growing media treated with Trichoderma yielded a 36% higher success rate for topgrafting. The oblique grafting method yielded a higher success rate of 39%, compared to the center grafting method, which had a success rate of 14%.